Twin-arginine signal peptide attributes effective display of CD147 to filamentous phage - Thammawong P. (2014)
A novel phagemid (pTat8) was constructed in this study to improve the quality of a molecule displayed on filamentous phage. The twin-arginine translocation (Tat) pathway was chosen for transporting and integrating a CD147 molecule into a phage particle via gpVIII. The parent vector pComb8-CD147Ex was modified by substituting a Sec signal sequence (PelB) with a twin-arginine signal sequence from trimethylamine N-oxide reductase (TorA). The characteristics of the CD147 displayed on the phage particle were evaluated by Sandwich ELISA and Western immunoblotting. A Tat-dependent leader was found to be superior to the Sec leader for the phage display of CD147. Our findings further support the involvement of an Escherichia coli Tat translocase in mediating the integration of a hydrophobic transmembrane protein into the inner membrane. This modified phagemid will be useful in phage display technique when the correctly folded structure is required (i.e., antibody libraries and ligand-receptor tracing).